Stilistika Majas dan Citraan Puisi “Sunyi Yang Tak Habis-Habis” Karya Muhammad Asqalani Eneste - Umi Nur Baity; Anis Febriana Sita Hidayati (Literasi : Jurnal Kajian Keislaman Multi-Perspektif, 2022)
Poetry is literary work that has elements figure of speech and strengthen the poetic element. This study to describe of figure of speech and imagery in the poem "Sunyi Yang Tak Habis-Habis" by Muhammad Asqalani Eneste. The poem is contained in anthology Doxology published by Sarbikita Publishing in 2014. This study uses a stylistic approach. The research method used is descriptive analysis method combined with semiotics. Research data in the form of descriptive data in form of sentences, phrases, and words in poetry. The results showed that poetry using figure of speech and imagery varied. Based on the data analysis, it was found that the types of figure of speech were found, such as repetition, hyperbole, irony, rhetoric, and sarcasm. In addition, various images were also found, such as motion images, visual and auditory images, and feeling images. The imagery and figure of speech dominate the meaning and message conveyed.